Prediksi Peningkatan Laba Perusahaan Ritel Pada Semester Kedua Berdasarkan Dengan Kinerja Keuangan Perusahaan - Syahrijal Hidayat (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
In recent years, global economic competition is very tight. For companies that cannot compete in this global economic competition, it is feared that the company will experience a setback. One company that is very active in this global economic competition is a retail company. An increase or decrease in profit in retail companies is also known as profit growth or decrease. Measurement of profit increase in retail companies is generally based on the financial performance of the company in each semester. The measurement of increasing profits and company performance can illustrate the performance carried out by management in retail companies. In this study, it will be investigated whether the variables of total asset turn over, current ratio, net profit margin and debt to equity ratio in retail companies are based on the company's financial performance. The number of samples is 30 retail companies. Techniques in data analysis using classical assumption testing, coefficient of determination, t test, f test and multiple linear regression. The results of the research for the H1 and H2 hypotheses in the research test were rejected. Furthermore, the hypothesis H3 and H4 are accepted while for testing on H1, H2, H3 and H4 whether there is a relationship between all variables that have an effect on increasing profits is rejected.